2002
DOI: 10.1063/1.1469027
|View full text |Cite|
|
Sign up to set email alerts
|

Measurements of ultrastrong magnetic fields during relativistic laser–plasma interactions

Abstract: Measurements of magnetic fields generated during ultrahigh intensity (>1019 W cm−2), short pulse (0.7–1 ps) laser–solid target interaction experiments are reported. An innovative method is used and the results are compared with particle-in-cell simulations. It is shown that polarization measurements of the self-generated harmonics of the laser can provide a convenient method for diagnosing the magnetic field—and that the experimental measurements indicate the existence of peak fields greater than 340 MG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
57
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(58 citation statements)
references
References 27 publications
0
57
0
1
Order By: Relevance
“…A variety of mechanisms for generation of a quasi-static magnetic field have been discussed in the past, including the thermo-electric dynamo [17] and a ponderomotive force [18]. These mechanisms easily explain the appearance of the toroidal magnetic field, as shown in Fig.…”
Section: Discrete Symmetries and Generation Of The Poloidal Magnetic mentioning
confidence: 99%
“…A variety of mechanisms for generation of a quasi-static magnetic field have been discussed in the past, including the thermo-electric dynamo [17] and a ponderomotive force [18]. These mechanisms easily explain the appearance of the toroidal magnetic field, as shown in Fig.…”
Section: Discrete Symmetries and Generation Of The Poloidal Magnetic mentioning
confidence: 99%
“…On the other hand, since the end of the 1970s, experiments have demonstrated that strong quasi-steady magnetic fields are created in laser-produced plasmas [19]. This was an important result as it had often been assumed that the absence of magnetic field effects, which greatly affect heat transport, was a desirable feature of laser-produced plasmas [20].…”
Section: Introductionmentioning
confidence: 97%
“…[7][8][9][10] Also, since the end of the 1970s, experiments have shown that strong quasisteady magnetic fields are created in laser-produced plasma. 11 This was an important result as it had often been assumed that the absence of magnetic field effects, which greatly affect heat transport, was a desirable feature of laser-produced plasmas. 12 These measurements showed clearly that strong magnetic fields can be generated even in unmagnetized plasmas.…”
Section: Introductionmentioning
confidence: 99%